2011
DOI: 10.1074/jbc.m110.128512
|View full text |Cite
|
Sign up to set email alerts
|

Copper Promotes the Trafficking of the Amyloid Precursor Protein

Abstract: Accumulation of the amyloid ␤ peptide in the cortical and hippocampal regions of the brain is a major pathological feature of Alzheimer disease. Amyloid ␤ peptide is generated from the sequential protease cleavage of the amyloid precursor protein (APP). We reported previously that copper increases the level of APP at the cell surface. Here we report that copper, but not iron or zinc, promotes APP trafficking in cultured polarized epithelial cells and neuronal cells. In SH-SY5Y neuronal cells and primary cortic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
78
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 74 publications
6
78
1
Order By: Relevance
“…Previous findings showed that copper increases APP cell surface localization (58) and promotes APP trafficking from the Golgi to intracellular compartments and to the cell surface (32). This supports H147N-APP decreased post-Golgi trafficking because His 147 might be necessary for APP copper binding.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Previous findings showed that copper increases APP cell surface localization (58) and promotes APP trafficking from the Golgi to intracellular compartments and to the cell surface (32). This supports H147N-APP decreased post-Golgi trafficking because His 147 might be necessary for APP copper binding.…”
Section: Discussionsupporting
confidence: 66%
“…In cellular models, increased intracellular copper levels up-regulated APP expression (30) and promoted the non-amyloidogenic processing of APP (31). Moreover, APP trafficked from the Golgi to the plasma membrane exhibited a decreased endocytosis in response to copper (32). Conversely, a decrease in intracellular copper levels led to decreased APP expression (33) and increased amyloidogenic processing of APP (34).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…PrP C and APP bind copper through their extracellular domains (43,44), and PrP C may serve as a buffer for copper binding in the extracellular space, perhaps at the synapse (45). Indeed, expression levels of PrP C (43) and APP (46,47) have been shown to influence neural copper levels, placing PrP C and APP in the network of proteins that regulate neural copper homeostasis.…”
Section: Copper Signaling In Neurobiologymentioning
confidence: 99%
“…The same finding has been observed in HD experimental models involving excitotoxicity [14,23], suggesting that Cu could play a role at the onset of neuronal damage in HD. In contrast, other research groups have demonstrated that Cu exerts a neuroprotective effect in HD, Parkinson's disease (PD), and Alzheimer's disease (AD) experimental models regarding excitotoxicity and cell death [17,24,33,34]. In a previous work, our group showed that Cu administered i.p.…”
Section: Discussionmentioning
confidence: 69%